Implementasi Framework Bootstrap dalam Desain UI/UX Website Ma’had Tahfidz Qur’an Darussalam - Nanda; Eriene Dheanda Absharina; Zainal Effendi (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
This research aims to design the User Interface (UI) and User Experience (UX) of the Ma’had Tahfidz Qur’an Darussalam website by utilizing the Bootstrap framework. The study was motivated by the institution’s need for an official digital platform that is more structured and professional compared to social media, particularly for information dissemination and new student enrollment. The research employed the Waterfall model, focusing on the design and prototype stages. Data were collected through field observation, informal interviews with the institution’s administrators, and literature reviews related to UI/UX and Bootstrap implementation. The result is a prototype design of several key pages, including homepage, institution profile, gallery, ZIS (Zakat, Infaq, Sadaqah), announcements, contact, admin login and registration, as well as student registration form. The use of Bootstrap proved effective in producing responsive, consistent, and user-friendly interfaces. This study is expected to serve as a foundation for developing a more integrated online registration system while strengthening the professional image of Ma’had Tahfidz Qur’an Darussalam in the digital era.